2019
DOI: 10.5553/plc/258999292019001001003
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Democracy and Bureaucracy in the Low Countries

Abstract: Consensus democracy and bureaucracy in the Low Countries Taking Lijphart’s work on consensus democracies as our point of departure, we signal a major shortcoming in Lijphart’s focus being almost exclusively on the political hardware of the state structure, leaving little attention for the administrative and bureaucratic characteristics of governance systems. We propose to expand the Lijphart’s model which overviews structural aspects of the executive and the state with seven additional features of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In short, while interest mobilisation differs across government levels, also the variation in lobbying strategies reflects the multi-level structure of the Belgian polity. Moreover, the clear prominence of the administration as a lobbying target seems to be a persistent feature of neo-corporatist and consensual policymaking in Belgium (see also van den Berg et al, 2014;van der Meer et al, 2019). This finding matches the assessment of 'corporatist resilience' observed in other small European countries Christiansen et al, 2018).…”
Section: Figuresupporting
confidence: 68%
See 2 more Smart Citations
“…In short, while interest mobilisation differs across government levels, also the variation in lobbying strategies reflects the multi-level structure of the Belgian polity. Moreover, the clear prominence of the administration as a lobbying target seems to be a persistent feature of neo-corporatist and consensual policymaking in Belgium (see also van den Berg et al, 2014;van der Meer et al, 2019). This finding matches the assessment of 'corporatist resilience' observed in other small European countries Christiansen et al, 2018).…”
Section: Figuresupporting
confidence: 68%
“…While some longitudinal research conducted in other neo-corporatist European countries found that the parliament as a lobbying target has gained substantial importance since the heyday of corporatism (Gava et al, 2017;Rommetvedt et al, 2013), this seems to be less markedly the case in Belgium. Belgium is still characterised by a weak parliament, 'politicised' government administrations and large personal cabinets of ministers (van den Berg et al, 2014;van der Meer et al, 2019). Second, most contacts are initiated with the administration, especially at the subnational level.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Despite these contributions, we know little about their respective long-term stability prior to the twentieth century. For instance, while seagrasses have long been used as a building material [ 16 ] and are thought to be a key source of Blue Carbon storage [ 17 ], their role in supporting human ecosystems prior to steep declines by the early 1900s remains undocumented [ 18 ]. Likewise, while European eel populations have been decimated (a 98% decline) since 1980 [ 19 ], eels have long been harvested as a cosmopolitan, highly desirable food species [ 20 ].…”
Section: Introductionmentioning
confidence: 99%